Provisions and contingent liabilities: a comparison between Portugal and the United Kingdom - Reis, Laura Nunes dos (2016)
The main objective of this dissertation is to compare companies from Portugal and UK concerning disclosure of contingent liabilities and recognition of provisions, since these are considered a source of creative accounting and to drive a parallel between differences found and the culture system of each country. Data was retrieved from databases and hand collected from financial statements of listed companies covering 2010 to 2013. Findings reveal that there are statistically significant differences on the amounts disclosed as contingencies or recognized as provisions by Portuguese versus British companies. However, they do not confirm the tendency for higher recognition in Portugal or a preference for disclosure in UK as Grays’ hypotheses for high secrecy (transparency) and high conservatism (optimism) in countries with high (low) uncertainty avoidance as Portugal (UK) suggest, giving rise to practices more associated with creative accounting in Portugal. Furthermore, findings expose that provisions and contingencies have a negative association with share prices, yet only statistically significant for contingencies. However, provisions reveal to be statistical significant after adapting the model to comprehend the effect of a risk committee on board of directors. Besides, the existence of this committee is value relevant to investors but this relevance is notwithstanding mitigated when considering Portugal against the total sample. Lastly, the study concludes that investors do value provisions differently from contingencies, yet this is not applicable when companies have a committee for risks, in which case they place a similar trust to both recognized and disclosed items assuming less creative accounting practices.